A Bibliometric Analysis Based on Web of Science: Current Perspectives and Potential Trends of SMAD7 in Oncology - Huang, Xueying; Yang, Zhiying; Zhang, Jinning; Wang, Ruojiao; Fan, Jiahui; Zhang, Heng; Xu, Rong; Li, Xia; Yu, Siying; Long, Linna; Huang, He (Frontiers in Cell and Developmental Biology, 2022)
Background: The number of publications on SMAD7 in the field of oncology is increasing rapidly with an upward tendency. In most cases, the mechanisms of carcinogenesis usually relate to disorders of signaling activity. Considering the crucial role of SMAD7 in the crosstalk of multiple signaling pathways, it is necessary to clarify and define the dominant research topics, core authors and their cumulative research contributions, as well as the cooperative relationships among documents or researchers. Methods: Altogether, 3477 documents were retrieved from the Web of Science Core Collection with the following criteria: TS= (SMAD7 OR SMAD7-protein OR Small-Mothers-Against-Decapentaplegic-7) refined by WEB OF SCIENCE CATEGORY (ONCOLOGY) AND [excluding] PUBLICATION YEARS: (2021) AND DOCUMENT TYPES: (ARTICLE OR REVIEW) AND LANGUAGES: (ENGLISH) AND WEB OF SCIENCE INDEX: (Web of Science Core Collection. SCI), and the timespan of 2011 to 2020. Bibliometric visualization analysis was conducted with CiteSpace and VOSviewer. Results: The number of documents grew each year. A total of 2703 articles and 774 reviews were identified from 86 countries/regions, 3524 organizations, 928 journals and 19745 authors. China was the most prolific country, with 1881 documents. Contributions from China, the United States and Germany were the most substantial. The most influential author was Lan Huiyao at The Chinese University of Hong Kong, with 24 publications and 2348 total citations. The bibliometric analysis showed that multilateral cooperation among diverse institutions or investigators was beneficial to high-quality outputs. The keyword “PPAR-gamma” exhibited the strongest burst in recent years, suggesting a potent research focus in the future. Conclusion: Research on SMAD7 in oncology is continuously developing. Bibliometric analysis of published papers can provide an overview and identify potential research trends for further studies in this academic field.